PELAKSANAAN KEGIATAN MBKM KEWIRAUSAHAAN TERHADAP USAHA PAW PARTY - Aryon, Debora Christina; Utama, Louis; Sutantio, Angelia; Wilbert, Davin; Cynthia, Emelia; Cristian, Steven (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The implementation of MBKM Entrepreneurship activities is a highlight in efforts to develop entrepreneurial skills among students. This study reveals the implementation of MBKM Entrepreneurship in the context of the